2021
DOI: 10.1111/jgs.17275
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis, bisphosphonate use, and risk of moderate or worse hearing loss in women

Abstract: Background: Osteoporosis and low bone density (LBD) may be associated with higher risk of hearing loss, but findings are inconsistent and longitudinal data are scarce. Bisphosphonates may influence risk, but the relation has not been studied in humans. We longitudinally investigated associations of osteoporosis and LBD, bisphosphonate use, vertebral fracture (VF), hip fracture (HF), and risk of self-reported moderate or worse hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
0
14
0
2
Order By: Relevance
“…As described by the authors, smaller previous studies linking hearing loss to osteoporosis have not been conclusive. While the Curhan et al's study 4 shows an association, the sample sizes (60,821 and 83,078 women) and similar relative risk of decreased hearing in two separate cohorts strengthen their observations. For most participants, a validated biennial questionnaire was used to assess hearing loss and other data.…”
Section: Is Silence Golden… In This Context Not So Muchmentioning
confidence: 77%
See 1 more Smart Citation
“…As described by the authors, smaller previous studies linking hearing loss to osteoporosis have not been conclusive. While the Curhan et al's study 4 shows an association, the sample sizes (60,821 and 83,078 women) and similar relative risk of decreased hearing in two separate cohorts strengthen their observations. For most participants, a validated biennial questionnaire was used to assess hearing loss and other data.…”
Section: Is Silence Golden… In This Context Not So Muchmentioning
confidence: 77%
“…The Curhan et al's study 4 provides another tantalizing insight into the possible mechanisms of the hearing loss and therapies that may or may not be useful to diminish the onset/progression of the process. During the time of data accrual, 1992–2017, participants who received two of the oral nitrogen‐containing bisphosphonates, alendronate and risedronate, had the same relative risk of hearing loss as those who did not receive such drugs.…”
Section: Figurementioning
confidence: 99%
“…The occurrence time of abnormal bone metabolism of TS is about 20–30 years earlier than that of normal women, and the risk of fracture is about 25% higher than that of normal people ( 50 , 51 ). Previous studies have found that osteoporosis and low BMD can lead to HL, which may be associated with abnormal bone metabolism in the temporal bone, including loss of bone mass in the ossicular chain in the middle ear and osseous structures in the inner ear such as the bone labyrinth ( 15 17 , 52 ). Yueniwati ( 53 ) found that BMD of cochlea, ossicles, femur or spine was negatively correlated with hearing threshold, indicating that abnormal bone metabolism may lead to HL.…”
Section: Discussionmentioning
confidence: 99%
“…La pérdida auditiva asociada a osteoporosis ha sido descrita por diversos estudios. Uno de los más recientes, de carácter longitudinal, ha sugerido un riesgo aumentado de padecer pérdida auditiva incrementada en aquellos pacientes con densidad mineral ósea disminuida u osteoporosis 4 . La presencia de una disminución o pérdida de la audición en pacientes con osteoporosis podría explicarse de acuerdo con hallazgos en estudios animales, en los cuales se ha descubierto que la homeostasis ósea sería de gran importancia para la preservación de la integridad coclear neurosensorial así como de la audición misma 6 .…”
Section: Discussionunclassified
“…Los posibles mecanismos implicados en la pérdida auditiva asociada a esta enfermedad son la desmineralización sistémica del sistema esquelético que podría afectar el hueso temporal, la cápsula coclear y el sistema de conducción tímpano-osicular en el oído medio. A pesar de que múltiples estudios han revelado esta posible asociación entre la pérdida auditiva y osteoporosis 4,5 , poco se conoce sobre los posibles eventos otopatológicos en el hueso temporal. En el siguiente caso, se describen los hallazgos histopatológicos post mortem de hueso temporal en un paciente con antecedentes de osteoporosis y pérdida auditiva.…”
Section: Osteoporosis Bilateral Del Yunque Hallazgos Otopatológicos I...unclassified